2021
DOI: 10.1108/rpj-08-2020-0205
|View full text |Cite
|
Sign up to set email alerts
|

The influence of porosity, crystallinity and interlayer adhesion on the tensile strength of 3D printed polylactic acid (PLA)

Abstract: Purpose The purpose of this study is to understand how printing parameters and subsequent annealing impacts porosity and crystallinity of 3D printed polylactic acid (PLA) and how these structural characteristics impact the printed material’s tensile strength in various build directions. Design/methodology/approach Two experimental studies were used, and samples with a flat vs upright print orientation were compared. The first experiment investigates a scan of printing parameters and annealing times and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, it displays some limitations such as poor water solubility, and being frangible [19]. Owing to its good accessibility, PLA is currently one of the most broadly applicable biodegradable polymers for various uses in packaging, electronic industries, automotive industries, and prosthesis fabrication, substituting effectively for petroleum-based polymers [20,21]. Many trends in orthopedic practice and research have suggested that PLA is safe and nontoxic [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, it displays some limitations such as poor water solubility, and being frangible [19]. Owing to its good accessibility, PLA is currently one of the most broadly applicable biodegradable polymers for various uses in packaging, electronic industries, automotive industries, and prosthesis fabrication, substituting effectively for petroleum-based polymers [20,21]. Many trends in orthopedic practice and research have suggested that PLA is safe and nontoxic [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have extensively studied the manufacturing of PLA using MEX process such an in-process monitoring of temperature evolution, multiscale damage and fatigue modeling of PLA [ 46 , 47 , 48 ]. The influence of process parameters has also been investigated on the mechanical properties [ 49 ], impact resistance properties [ 50 ] and interlayer adhesion on the tensile strength of 3D printed PLA [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the printed specimens acted similarly to the natural lubrication mechanism of the meniscus. The porosity of FDM prints has been studied by other authors, although in the context of mechanical properties rather than tribological properties [36][37][38]. Moreover, the porosity of 3D prints is seen as a great chance to produce scaffolds that promote tissue growth [39][40][41].…”
Section: Introductionmentioning
confidence: 99%